2004
DOI: 10.1002/dvdy.20158
|View full text |Cite
|
Sign up to set email alerts
|

Two DM domain genes, DMY and DMRT1, involved in testicular differentiation and development in the medaka, Oryzias latipes

Abstract: The recent discovery of the DMY gene (DM domain gene on Y chromosome and one of the DMRT1 family genes) as a key determinant of male development in the medaka (Oryzias latipes) has led to its designation as the prime candidate gene for sex-determination in this species. This study focused on the sites and pattern of expression of DMY and DMRT1 genes during gonadal differentiation of medaka to further determine their roles in testis development. DMY mRNA and protein are expressed specifically in the somatic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
242
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 289 publications
(263 citation statements)
references
References 46 publications
(53 reference statements)
16
242
3
2
Order By: Relevance
“…A recent report on a study using chickens showed that ZW sex reversal from female to male was accompanied by DMRT1 expression in medullary cells, which developed into Sertoli cells (Smith et al, 2003). Furthermore, our recent study indicates that medaka DMRT1 is expressed in the germ-cell-surrounding cells and the intratesticular efferent duct, al- though medaka DMRT1 is expressed after testicular differentiation, unlike in tilapia (Kobayashi et al, 2004). In medaka, however, sex determining gene DMY, a DMRT1 orthologue, is expressed in germ-cell-surrounding cell lineage cells before sex differentiation (Kobayashi et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…A recent report on a study using chickens showed that ZW sex reversal from female to male was accompanied by DMRT1 expression in medullary cells, which developed into Sertoli cells (Smith et al, 2003). Furthermore, our recent study indicates that medaka DMRT1 is expressed in the germ-cell-surrounding cells and the intratesticular efferent duct, al- though medaka DMRT1 is expressed after testicular differentiation, unlike in tilapia (Kobayashi et al, 2004). In medaka, however, sex determining gene DMY, a DMRT1 orthologue, is expressed in germ-cell-surrounding cell lineage cells before sex differentiation (Kobayashi et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, our recent study indicates that medaka DMRT1 is expressed in the germ-cell-surrounding cells and the intratesticular efferent duct, al- though medaka DMRT1 is expressed after testicular differentiation, unlike in tilapia (Kobayashi et al, 2004). In medaka, however, sex determining gene DMY, a DMRT1 orthologue, is expressed in germ-cell-surrounding cell lineage cells before sex differentiation (Kobayashi et al, 2004). Taken together, these results indicate that DMRT1 is expressed in Sertoli-celllineage cells specifically, suggesting that the findings from human, bird, and reptile models are consistent with the results for tilapia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using gene expression profiling and ISH, we were able to demonstrate that gonadal differentiation occurred much sooner, i.e., shortly after hatching and at least one month before the first signs of morphological gonadal differentiation. In fish, this early molecular differentiation period has been poorly investigated and is only well documented in the medaka, Oryzias latipes, with the early testicular expression of the DM domain gene, dmy (Kobayashi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%